Penggunaan Media Kincir Huruf Untuk Meningkatkan Kemampuan Pengenalan Huruf Pada Anak Usia Dini - Rahma Rahma; Sari Rizki; Agustina Agustina; Dwi Adhinda Junaidi Putri; Hendri Wan Prala (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine, 1) To find out how the process of improving the ability to recognize letters in early childhood after the implementation of the letter pinwheel media in Sirajul Huda Kindergarten, Jeumpa District, Bireuen Regency. 2) To determine the activities of teachers and students in improving the ability to distinguish letter sounds, letter shapes through the letter pinwheel media in Sirajul Huda Kindergarten, Jeumpa District, Bireuen Regency. This study is classroom action research using qualitative data analysis. The subjects in this study were children in group B of Sirajul Huda Kindergarten, totaling 7 boys and 8 girls. The data collection method was carried out through performance, observation and documentation. Based on the research results, it showed that the students’ ability in recognize letters was increase from cycle I (40%) become 80% in cycle II. Meanwhile, the percentage of teacher’s performance in cycle I wa 62%, including the